Vascular Calcification: Is it rather a Stem/Progenitor Cells Driven Phenomenon? - Leszczynska, Aleksandra; Murphy, J. Mary (Frontiers in Bioengineering and Biotechnology, 2018)
Vascular calcification has witnessed a surge of interest. Vasculature is virtually an omnipresent organ and has a notably high capacity for repair throughout embryonic and adult life. Of the vascular diseases, atherosclerosis is a leading cause of morbidity and mortality on account of ectopic cartilage and bone formation. Despite the identification of a number of risk factors, all the current theories explaining pathogenesis of vascular calcification in atherosclerosis are far from complete. The most widely accepted response to injury theory and smooth muscle transdifferentiation to explain the vascular calcification observed in atherosclerosis is being challenged. Recent focus on circulating and resident progenitor cells in the vasculature and their role in atherogenesis and vascular calcification has been the driving force behind this review. This review discusses intrinsic cellular players contributing to fate determination of cells and tissues to form ectopic cartilage and bone formation.